Performance Analysis of Single-Stage and Two-Stage VSI-Fed Induction Motor Drives for Solar Water Pumping Applications - Maurya J.; Saket R.K.; Srivastava R.K. (My University, 2025)
This paper describes a comparative performance analysis of single-stage and two-stage voltage source inverter (VSI) fed induction motor (IM) drive for water pumping systems used in agricultural applications. The comprehensive analysis with illustrative descriptions of proposed research is conducted to evaluate the system's economic viability for a solar pump based irrigation system. These two setups share common components, including photovoltaic (PV) system, battery with bidirectional converter and VSI-fed IM drives with pump load. In both configurations, incremental conductance (INC) maximum power point tracking technique (MPPTT) is employed to extract maximum power from the PV array. In two stage system, a DC/DC boost converter is integrated to elevate the input voltage for VSI and meet the system's load requirements. On the other hand, in single-stage system, PV array is directly connected to VSI, which provides power to entire IM drive integrated with pump. A direct torque control (DTC) strategy is utilized for speed regulation of IM drive in both setups, ensuring that the characteristics of PV array-fed IM drive with pump load are maintained. An insightful efficiency versus load analysis has been presented for power electronics system and IM drive, which shows comparative efficiency and thermal characteristics between both configurations, shedding light on optimal system design for enhanced performance. Typhoon HIL 404 software is used for modelling and simulation of the systems. The real-time hardware results have been taken by using HIL Device and 4 Series B mixed signal oscilloscope (MSO) for validation of the simulation results. The comparative performance analysis, graphical illustrations and performance descriptions between a single-stage PV fed IM drive and two-stage PV fed IM drive are described in simulation results and experimental validation sections. © 1972-2012 IEEE.